MODIFIKASI DINDING BUBU LIPAT UNTUK MELOLOSKAN RAJUNGAN YANG BELUM LAYAK TANGKAP: Collapsoble Trap Wall Modification to Realease Under Size Blue Swimming Crab - Susanto, Adi; Sutrawan Nurdin, Hery; Jayanudin; Irnawati, Ririn; Hamzah, Asep; Supadminingsih, Fahresa Nugraheni; Syafrie, Hendrawan; Azkia, Lana Izzul; Sucilawati, Mumung; Adisaputra, Divandra Yogi; Hikmatyar, Alfito Dicky (Bogor Agricultural University, 2024)
Increasing of fishing pressure poses a serious threat to the sustainability of blue swimminng crab resources. Trap design modifications are needed to improve size selectivity and to release under size crabs. This study aimed to determine the type of wall modification of collapsible trap that is effective in excluding under size blue swimming crab. Laboratory observations were conducted using four escape vents treatments and three different mesh sizes. The escape gap used are rectangular, square, circular and oval respectively. Moreover, the mesh sizes used are 2.0 inches, 2.5 inches and 3.0 inches. Descriptive analysis and scoring were used to determine the most effective type of wall trap modification to be used in the blue swimming crab fishing. The results showed that the rectangular escape gap has better effectiveness than other shapes with the percentage of crabs that pass through at 86.7%. The wall modification using a 3.0-inch mesh size had better performance than the other modification types with a total score of 19. Collapsible trap with a 3.0-inch mesh wall was able to escape 86.7% of the crabs with an escape time of only 11.2 seconds and an average escaped crab carapace width of 78 mm. Keywords: Collapsible trap, escape gap, environmentaly-frendly fisheries, mesh size of trap wall